Antimicrobial Photodynamic Therapy for the Treatment of Alveolar Osteitis in a Patient With Acute Lymphoid Leukemia: A Case Report: a-PDT to Treat Alveolar Osteitis in Patient With Leukemia - Camilo-Silva, Gabriela; A Melo, Sara Maria; do Couto Lima Moreira, Francine; C Campos, Cerise; Roriz, VirgÃlio M. (Journal of Lasers in Medical Sciences, 2021)
Introduction: Acute lymphoid leukemia (ALL) is a malignant disease, the prognosis of which depends on the age of the patient and the treatment. The aim of this article was to report the treatment of this rare and interesting case of alveolar osteitis with antimicrobial photodynamic therapy (aPDT) in a patient with ALL that was resolved efficiently and quickly. Case Presentation: A 33-year-old male diagnosed with ALL attended the public service, complaining of pain in the region of tooth 48, without function. Extraction was performed, and the patient returned for postoperative follow-up, complaining of severe pain in the area of the alveolus. Clinical examination revealed osteitis. The alveolus was treated using aPDT with 0.005% methylene blue photosensitizer, followed by the application of a low-level red laser at a wavelength of 660 nm (321J/cm2– site). After 15 days, soft tissue closure was observed and complete filling of the alveolus was observed radiographically with a 7-month follow-up. Conclusion: The authors suggest that aPDT can be an effective treatment of alveolar osteitis in a patient with ALL. DOI: 10.34172/jlms.2021.79.